PEMBUATAN LAPISAN TIPIS TiO2 -DOPED LOGAM M (M= Ni, Cu dan Zn) DENGAN METODA DIP-COATING DAN APLIKASI SIFAT KATALITIKNYA PADA PENJERNIHAN AIR RAWA GAMBUT - Syukri Arief; Admin Alif; Nancy Willian (Jurnal Riset Kimia, 2008)
ABSTRACT Preparation of TiO2-doped M (M = Ni, Zn and Cu) has been prepared on glass substrate using dip-coating technique. Titanium isopropoxide (TIP), Ni(OAct)2.4H2O, Zn(OAct)2.2H2O dan Cu(OAct)2 were used as starting materials and diethanolamine (DEA) as additive in isopropanol solution. Solutions were prepared by mixing of various concentration of metals (1, 3 and 5 mol %)  in 0.5 M TIP solution. Thin films were performed by immersion of glass substrate into solution by withdraw speed of 20 cm/min. Coated glass were dried at 100 – 110°C and heated at 500°C the process were repeated for several time. The product was characterized by XRD and showing TiO2 layer of anatase structure. EDX analysis has shown that thin films have found of Ti and doped-metal. Their crystallized sizes were calculated by Scherrer formula shown that it obtained in various in range of 12-21 nm. According to transformation effectively of titania doped M in peat swam water shown that catalytic activity 34.4 – 53.7% for the irradiation during 24 hours. Keywords : titania, thin films, photocatalytic properties